The effect of barium titanate ceramic loading on the stress relaxation behavior of barium titanate‐silicone elastomer composites. Issue 12 (30th September 2020) - Cholleti, Eshwar Reddy; Stringer, Jonathan; Kelly, Piaras; Bowen, Chris; Aw, Kean
Abstract: The stress relaxation behavior of barium titanate (BTO)‐elastomer (Ecoflex) composites, as used in large strain sensors, is studied using the generalized Maxwell‐Wiechert model. In this article, we examine the stress relaxation behavior of ceramic polymer composites by conducting stress relaxation tests on samples prepared with varying the particle loading by 0, 10, 20, 30, and 40 wt% of 100 and 200 nm BTO ceramic particles embedded in a Ecoflex silicone‐based hyperelastic elastomer. The influence of BTO on the Maxwell‐Wiechert model parameters was studied through the stress relaxation results. While a pristine Ecoflex silicone elastomer is predominantly a hyperelastic material, the addition of BTO made the composite behave as a visco‐hyperelastic material. However, this behavior was shown to have a negligible effect on the electrical sensing performance of the large strain sensor. Abstract :